2004
DOI: 10.1080/0307945042000220426
|View full text |Cite
|
Sign up to set email alerts
|

The isolation and characterisation of astroviruses from chickens

Abstract: The isolation, cultivation and characterization of three chicken astroviruses (CAstV) isolates are described. They are antigenically related to each other but unrelated to avian nephritis virus (ANV) and duck hepatitis virus type 2 (DVH2) in neutralization, immunofluorescence and gel diffusion tests. CAstV, ANV and DVH2 all grew well in the LMH cell line, which was used for assay and serological tests. Serological surveys in 1982 and 2001 showed that antibody to CAstV virus was widespread in broiler and broile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
130
0
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(138 citation statements)
references
References 14 publications
2
130
0
6
Order By: Relevance
“…On the basis of antigenic and genetic relatedness shared with a reference CAstV isolate, first described by Baxendale & Mebatsion (2004), the ELV-3 and ELV-4 isolates can be regarded as different isolates of CAstV. Based on ORF 1b sequence comparisons, this work has also shown that ELV-1 represents an isolate of ANV, that the astrovirus DHV-2 is distinct from other avastroviruses, and that DHV-3 can also be identified an avian astrovirus.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…On the basis of antigenic and genetic relatedness shared with a reference CAstV isolate, first described by Baxendale & Mebatsion (2004), the ELV-3 and ELV-4 isolates can be regarded as different isolates of CAstV. Based on ORF 1b sequence comparisons, this work has also shown that ELV-1 represents an isolate of ANV, that the astrovirus DHV-2 is distinct from other avastroviruses, and that DHV-3 can also be identified an avian astrovirus.…”
Section: Discussionmentioning
confidence: 82%
“…The P22 18.8.00 isolate of CAstV, hereafter named the reference CAstV isolate, was obtained from Dr I. Tarpey, Intervet, Milton Keynes, UK. This virus, which was originally isolated and propagated in chick embryo liver (CEL) cells (Baxendale & Mebatsion, 2004), was passed twice in CEL cells before use in this investigation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These have involved the application of indirect IF tests (McNeilly et al, 1994;Todd et al, 2009b) and a virus neutralization (VN) test, which was based on the first characterized CAstV isolate (Baxendale & Mebatsion, 2004). The use of an ELISA for detecting CAstV antibodies in experimentally vaccinated chickens was also described by Sellers et al (2010).…”
Section: Discussionmentioning
confidence: 99%
“…CAstV was first characterized as a novel astrovirus by Baxendale and Mebatsion (2004), who reported the isolation of three antigenically similar viruses, exemplified by the P22-18.8.00 isolate, from outbreaks of runting stunting syndrome that occurred in the Netherlands in the 1980s. Since then CAstVs have been detected by reverse transcription-polymerase chain reaction (RT-PCR) in intestinal samples from growth-retarded and normal broilers reared in the USA, India, UK and other European countries Smyth et al, 2009Smyth et al, , 2010Bulbule et al, 2013).…”
Section: Introductionmentioning
confidence: 99%